The north gap dyke of the Transkei - Moore, Alan C (Rhodes University, Faculty of Science, Department of Geology, 1964)
Field work and mapping with the aid of aerial photographs have shown the north Gap Dyke to be a vertical intrusion 93Â½ miles long . It extends from a point about 4Â½ miles south of Cathcart to the coast where it enters the sea about 100 yards north of the Ngadla R lver mouth. It is composed of several rock types including dolerite pegmatite, granophyric dolerite, subophitic dolerite, and it has a more or less central core of mobilized sediment at the western end. The essential minerals of the dolerite types include zoned plagioclase, which is described in some detail, and augite. Less important are hornblende and micropegmatite. Accessories include apatite, ilmenite, magnetite, quartz, actinolite, prehnite, calcite and epidote. Iddingsite (?), saussurite and chlorite occur as alteration products. The mode of origin of the Gap Dyke magma remains an open question: it may have arisen as a result of normal crystal fractionation or as the result of hybridization in depth followed by differentiation.
Keywords: Petrology -- South Africa -- Transkei; Dikes (Geology) -- South Africa -- Transkei; Petrofabric analysis -- South Africa -- Transkei